The Instructional Media Criteria In English Learning Videos On The Ruang Guru Youtube Channel - Rusmadi Rusmadi; Ventje Kalukar; Anjar Dwi Astuti (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2021)
This study focused on three English learning videos on the Ruang Guru Bimbel Online No. 1 YouTube channel. The design of this research is descriptive qualitative. The subjects of this study were three videos from the Ruang Guru Bimbel Online No. 1 YouTube channel which discusses the expression material for junior high school, as well as the responses from viewers in the three videos. This study used a checklist observation sheet and viewers' comments as documents to collect data. Researchers used a checklist of instructional video criteria adapted from Dimas, et al. (2018) to determine the criteria applied by the Ruang Guru Bimbel Online No. 1 YouTube channel. The researcher also used viewers' comments to find out the audience's response to the instructional video. The researcher found that the videos from the Ruang Guru Bimbel Online No.1 YouTube channel is a useful video and the content already contains a learning model that is in accordance with the 2013 curriculum, and also there is no gender discrimination in the videos which are in accordance with the first criterion, namely content. then there is a motivating introduction, detailed information to be understood, suggested methods that can be used by teachers, can be used as teacher reflections, activities that can encourage active learning, and the audio-visual quality is quite clear which is in accordance with the second and third criteria, namely instructional plans, and technical production. On the fourth criterion, which is included supplement materials, the researcher did not find any supplemental materials from the videos. Then most of the responses found from viewers lead to positive responses to the Integration into the Learning Environment on the Instructional Plan criteria, where viewers think these videos can be used as independent learning or in class. As for the negative response aimed at audio quality in the Technical Production criteria, the viewers felt that the teacher was still lacking in the pronunciation aspect.